The Influence of Brand Value on Tax Avoidance with Ownership Concentration as a Moderating Variable - Elisa Tjondro; Felincia Puguh Mitthasari Utomo; Celine Mercianne Susila; Oviliani Yenty Yuliana (Jurnal Ilmiah Akuntansi dan Bisnis, 2024)
The present investigation was prompted by different viewpoints on evaluating the effect of brand value on either the promotion or prohibition of tax avoidance strategies. Using the Agency Theory framework, it also intends to investigate how the concentration of ownership affects the relationship between brand value and tax avoidance strategies of enterprises listed in Indonesia. Researchers believe that by merging these studies and viewpoints, the ruling shareholders will emphasize managerial scrutiny to minimize tax avoidance and protect the company’s brand. The sample used in this research is based on 151 observations of 47 entities listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. А panel regression with a random effects model was employed in the present research. The endpoint of this research is to look at the impact of brand value on tax avoidance and the role of ownership concentration as a moderator in the association between brand value and tax avoidance. The results suggest that the increasing brand value contributes to reducing tax avoidance. This study also finds that ownership concentration significantly impacts the relationship between brand value and tax avoidance.